2009
DOI: 10.1038/mp.2008.122
|View full text |Cite
|
Sign up to set email alerts
|

Findings from bipolar disorder genome-wide association studies replicate in a Finnish bipolar family-cohort

Abstract: and rs1170191 were quite similar in the Baum et al. 3 and in our control samples, allele frequencies of rs9315885 were moderately different (T-allele frequency: mean of the two samples = 0.67, Baum et al. 3 ; our sample = 0.53). Differences in allele frequencies might be explained by the fact that although Baum et al. 3 and our samples were both of Caucasian ancestry, our sample was consisting of subjects of Sardinian ancestry for at least four generation.In conclusion, the association for a DGKH haplotype rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
59
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 10 publications
4
59
0
1
Order By: Relevance
“…6 We also tested these three SNPs and identified nominal evidence of association to BP with rs7683874 (P = 0.024) and rs10937823 (P = 0.031), but with the opposite alleles conferring the increase in risk. In a replication study of the 26 SNPs with strongest association from the three GWAS of BP, Ollila et al 7 also reported nominal association to these three SORCS2 SNPs (best P = 0.0042) in a Finnish familybased cohort, with the same alleles as in our study conferring the increase in risk. Although this 'flip-flop' association may suggest spurious findings, it could also be a result of allelic heterogeneity, multi-locus effects or variable LD patterns between the samples, as, for example, observed between the GAPDH gene and Alzheimer's disease, owing to the variable interlocus correlation between the GAPDH and APOE e4 alleles in two different samples.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…6 We also tested these three SNPs and identified nominal evidence of association to BP with rs7683874 (P = 0.024) and rs10937823 (P = 0.031), but with the opposite alleles conferring the increase in risk. In a replication study of the 26 SNPs with strongest association from the three GWAS of BP, Ollila et al 7 also reported nominal association to these three SORCS2 SNPs (best P = 0.0042) in a Finnish familybased cohort, with the same alleles as in our study conferring the increase in risk. Although this 'flip-flop' association may suggest spurious findings, it could also be a result of allelic heterogeneity, multi-locus effects or variable LD patterns between the samples, as, for example, observed between the GAPDH gene and Alzheimer's disease, owing to the variable interlocus correlation between the GAPDH and APOE e4 alleles in two different samples.…”
mentioning
confidence: 69%
“…5 The genetic risk factor for PD used in this study was the C allele of the 102T/C single-nucleotide polymorphism (rs6313) within the serotonin 2a receptor gene (HTR2A) on chromosome 13q14.2; the C allele in this SNP is known to be associated with increased susceptibility to pure but not co-morbid PD, 6 as well as to increased intensity of panic symptoms. 7 All 200 participants (107 of whom were male) gave informed consent and self-identified as healthy Caucasians. Buccal cells were collected and DNA extracted using established methods (see Supplementary Information).…”
mentioning
confidence: 99%
“…Finally, also including meta-analytic treatment of the WTCCC and Sklar data sets found strong evidence for CACNA1C (a-1 subunit of a voltage-dependent calcium channel) and ANK3 (ankyrin 3) . Taken together, these GWAS have provided risk genes that have been replicated in some cases (DGKH (Baum et al, 2008b;Ollila et al, 2009); SORCS2 and DFNB31 (Ollila et al, 2009); CACNA1C ); ANK3 (Lee et al, 2010;Schulze et al, 2009;Scott et al, 2009;Smith et al, 2009); TSPAN8 (Scholz et al, 2010)), while other replication attempts were negative. Several promising hits, however, were never attempted to replicate, and the potential impact of these candidate genes on other disorders displaying by mood disturbance has not yet been assessed.…”
Section: Introductionmentioning
confidence: 91%
“…SLC39A8 was selected from our previous GWAS of missense SNPs (Carrera et al, 2012). SLC39A3 was selected due to the hypothesis generated in our previous GWAS of missense SNPs that brain metal homeostasis may be involved in pathology of schizophrenia as well as its putative role in psychiatric disorders (Baum et al, 2008;Ollila et al, 2009). CNTNAP2 and NRXN1 were selected due to their association with schizophrenia based on CNV data (Friedman et al, 2008;Vrijenhoek et al, 2008).…”
Section: Genesmentioning
confidence: 99%